Cercetările de diagnoza calității vieții în cadrul Institutul de Cercetare a Calității Vieții - Mărginean, Ioan (Calitatea Vieții, 2020)
In the first year of activity (1990) at the Research Institute for Quality of Life (Institutul de Cercetare a Calităţii Vieţii, INCE, Academia Română) it was starting the research of quality of life. It was prepared by the collective coordinated by Professor Cătălin Zamfir, director of RIQL. I participated at this work a starting with field research (june 1990), I was coordinated, most of the time together with some colleagues, the activity for this program. The experience achieved during the years in this domain will be used here to reveal the aspects of the researches and results about Quality of Life of population in Romania. Over time, many indicators of Quality of Life have registered some improvements, but also stagnations, and even deterioration of several components.